Pengaruh Penggunaan E-Wallet, Literasi Keuangan, dan Kemudahan Teknologi Terhadap Perilaku Konsumtif Masyarakat: The Influence of E-Wallet Use, Financial Literacy, and Technological Convenience on Consumer Behavior - Salsabila Maulida Azzahra; Arini Nur Putri Alam; Hayfa Nafisa Husne Ara; Nabila Aprilia; Raisya Fitri Ramadhani; Rudianto Rudianto (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
The development of digital technology has driven significant changes in public transaction patterns, one of which is through the use of electronic wallets (e-wallets). The convenience, speed, and various promotions offered by e-wallets have the potential to influence consumers’ consumptive behavior. In addition, the level of financial literacy plays an important role in determining how individuals manage their spending and make financial decisions. This study aims to analyze the effect of e-wallet usage, financial literacy, and technological convenience on consumers’ consumptive behavior. The research method used is a quantitative approach, with data collected through questionnaires distributed to respondents who use e-wallets. The data were analyzed using statistical analysis techniques to examine the influence of each independent variable on consumptive behavior. The results show that e-wallet usage and technological convenience have a positive effect on consumers’ consumptive behavior, while financial literacy has a negative effect, indicating that the higher a person’s financial literacy, the lower the tendency toward consumptive behavior. These findings are expected to serve as a consideration for the public and policymakers in improving financial literacy and encouraging more responsible use of financial technology.